Standardizing the endorsement process in the Customer Operations Department of AMP Marine Products - Galera, Marcelle Josephine M. (Animo Repository, 2021)
System updates can render existing business processes obsolete. When AMP Marine Products transitioned from SAP-CRM to Salesforce as its customer relationship management system, its incumbent endorsement process was deemed unusable as the new system no longer supported the process, thereby creating an opportunity for a new endorsement process. The goal of this action research was to implement an endorsement process that utilizes the features of Salesforce. The action research applied the Model-based and Integrated Process Improvement (MIPI) Methodology as its conceptual frameworks. The first cycle of this action research focused on the creation, implementation and evaluation of the new endorsement process. Process mapping was used in creating the process and engaging the stakeholders. Qualitative evaluation was employed to evaluate the impact of the new process. The feedback was generally positive whereby the users conveyed that it supported faster sending and returning of endorsements, easier management of endorsed cases and quicker response to customer queries. On the other hand, there were significant areas for improvement that were shared by the users namely, the lack of audit trail, lack of prompt and premature closing of a case. These areas for improvement were addressed in the second cycle whereby controls were put in place to serve as the audit trail and prompt for an endorsement in the form of a screenshot of all endorsed transactions. The premature closing of the case triggered a reinforcement of the agreed process but did not require an amendment on the process. The screenshots were deemed by the users as an additional step but were necessary for audit trails and prompts. The interventions made in the first and second cycle of this action research enabled us to meet the objective of the project.